A systemic approach to applying asset orchestration theory. (2018) - Mansoor, Hamdan O.; Weston, Richard H.; Abdullah, Rohana; King, Steven; Jackson, Peter; Foley, Paul
The paper proposes and uses a reference model of asset orchestration which characterises common organising relationships observed between the 'resource-based view' and the 'dynamic capabilities view' of firms. This reference model helps to visualise and communicate alternative common decision-making contexts needed to sustain competitive responses in firms through their lifetime, and thereby through the lifetime of the products and the services they realise. Little present literature describes the practical application of emergent asset orchestration (AO) concepts. Hence, the present authors use their reference model to capture actual AO data within two case study firms. The captured data shows how AO theory can be deployed to direct strategic decision making towards sustainable configuration and deployments of a firms resource portfolio. Essential characteristics of the new reference model and of how it can be applied are reported in this paper.